Irrigant selection for treating trauma wounds on injured wildlife patients - Atkinson, Kariana; McRuer, Dave (Wildlife Rehabilitation Bulletin, 2021)
<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Contaminated wounds are frequently encountered on injured wildlife patients. Left untreated, contaminated wounds may result in infection with ongoing complications. Wound irrigation is an essential part wound treatment and arguably the most effective means of preventing wound infection. Successful treatment depends on a number of factors but selecting the most appropriate irrigant for the type of wound, degree and type of contamination, species and patient status is up to the informed caregiver. This article discusses some of the pros and cons of common irrigants used in veterinary wound management and best practices for application.